2022
DOI: 10.1002/ece3.9454
|View full text |Cite
|
Sign up to set email alerts
|

How do introductory field biology students feel? Journal reflections provide insight into student affect

Abstract: An understanding of both cognitive and affective domains of learning is critical to promoting undergraduate student success in biology. Field courses—which support student learning, observation, and experimentation in the outdoors—have been shown to be effective in supporting cognitive student outcomes. However, less is known about students' affective responses during field instruction. To better understand the affective domain in this course type, we asked students enrolled in a campus‐based introductory fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 147 publications
(230 reference statements)
0
7
0
Order By: Relevance
“…While students reached out to TAs and instructors for personal support on occasion, they mainly sought personal support from their research partners. Students who engage in field courses can gradually develop collaborative relationships with their classmates and build rapport by participating in shared experiences (Race et al, 2021; Treibergs et al, 2022). Therefore, it is possible that students built enough rapport to seek personal support from their research partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While students reached out to TAs and instructors for personal support on occasion, they mainly sought personal support from their research partners. Students who engage in field courses can gradually develop collaborative relationships with their classmates and build rapport by participating in shared experiences (Race et al, 2021; Treibergs et al, 2022). Therefore, it is possible that students built enough rapport to seek personal support from their research partners.…”
Section: Discussionmentioning
confidence: 99%
“…Further, participation in field courses can promote students' knowledge growth, spatial reasoning, and familiarity with the scientific process (Mason et al, 2018;Riggs et al, 2009). They also can support students' affective development (O'Connell et al, 2021(O'Connell et al, , 2022Shinbrot et al, 2022;Treibergs et al, 2022). For example, field courses can promote developments in students' motivation (Scott et al, 2019) and science self-efficacy (Beltran et al, 2020), and can further increase students' confidence to engage in fieldwork (Peacock et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We collected student field journal reflections, which were also used to develop the Framework of Student Affect in Field Biology (Treibergs et al, 2022). Keeping a detailed field notebook is part of the culture and practice of field biology.…”
Section: Methodsmentioning
confidence: 99%
“…Field courses—which empower students to engage in disciplinary practices and learn skills and concepts while immersed in outdoor settings—are important components of natural scientific disciplines, including the life sciences (Fleischner et al, 2017; Zavaleta et al, 2020) and geosciences (Kirkby, 2014; Riggs et al, 2009). When purposefully designed, field courses can promote equity and inclusivity (Zavaleta et al, 2020) and can bolster outcomes linked to retention, such as positive affect (Treibergs et al, 2022), knowledge (Patrick, 2010), self‐efficacy, grades, and graduation rates (Beltran et al, 2020). Furthermore, fieldwork experiences in life science and geoscience have been shown to promote productive formal and informal social interactions between students and their instructors (Cotton, 2009; Posselt & Nuñez, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, reflective thinking enables individuals to identify their personal strengths and weaknesses and to develop effective solutions to problems encountered ( Mamlok-Naaman & Eilks, 2012;Ho & Smith, 2021;Alt et al, 2022). Extensive research has demonstrated that reflective thinking is instrumental in enhancing students' task performance (Oliveira et al, 2021;Treibergs et al, 2022;Yang et al, 2022). However, previous studies on reflective thinking have been criticized for their limited scope, highlighting the need for further research to establish a fundamental framework for reflective thinking and practice in science education.…”
Section: Reflective Thinkingmentioning
confidence: 99%